Lemierre's syndrome with muscle necrosis and chronic osteomyelitis. Issue 3 (4th May 2021) - Latif, Azka; Ahsan, Muhammad Junaid; Yousaf, Amman; Tameezuddin, Asim; Sood, Akshat; Thirumalareddy, Joseph
Abstract: Lemierre's syndrome is a rare disorder characterized by thrombophlebitis of the internal jugular vein and is caused by gram-negative anaerobes, primarily Fusobacterium necrophorum . We report a case of a 20-year-old man who developed chronic osteomyelitis of the femur and myonecrosis of thigh muscles secondary to this syndrome. The diagnosis was made based on clinical presentation and evidence of thrombosis in the internal jugular vein on ultrasound. The patient was initially treated with antibiotics, and anticoagulants were added later due to deep vein thrombosis in the lower limb.